Re-Design of Riau Malay Songket Packaging Using Kansei Engineering Method - Ulfadiah, Nurul; Yola, Melfa; Hamdy, Muhammad Ihsan; Umam, Muhammad Isnaini Hadiyul; Harpito, Harpito (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2026)
Songket is an attribute of the Riau region worn by men from the Malay tribe. Not only as an attribute of regional clothing, songket is marketed as a souvenir from Riau province. The conditions stated on the songket packaging are very simple, using Oriented Polyproylene plastic packaging material without any packaging design. Meanwhile, as a souvenir product for private agencies and government officials, packaging is required to represent the product. Packaging design based on consumer desires and needs can use the Kansei Engineering method which is used in product development to achieve consumer satisfaction by analyzing human feelings and emotions and pouring them into product design. Collected and distributed to 68 respondents. Respondent responses were subjected to statistical tests and factor analysis with the results showing that there were 9 statements with values above 0.5, namely rectangular, packaging has been formed and ready to use, typical Riau Malay colors, displays business information, and songket motifs as a characteristic of Riau province. After getting the packaging design concept, consultations were carried out with experts. Professional consultations were carried out with people who have knowledge of packaging design, material needs, prices or experts in the field of songket weaving. The packaging design that has been carried out produces a packaging design according to consumer needs to attract consumer buying interest and describe it as a typical product of Riau province in choosing Malay songket products as souvenirs.